The true myth – can a university lecture be interactive? - Major Éva („RIK-U” Kft., 2018)
Abstract. There is an increasing interest in higher education to transcend from traditional teacher-focused, didactic teaching to more student-focused methods which are more engaging and attractive for students especially because learning preferences seem to have changed. However, simultaneously there are also increasing student numbers and thus, it is important to develop and implement ways of teaching that can simultaneously serve large numbers of students while more actively engaging them in the learning process. I would like to begin with an experiment I did with my own students at ELTE. I had asked them (about 30 students) to list words or expressions in two columns. In the first column about ‘their ideal learning environment’ (under what circumstances do they learn best?) and in the other about ‘university lectures’. What came out are two lists that I have converted into word clouds. In the first word cloud (ideal learning environment) the most frequent words were: silence, alone, home, interactive, active, loudly, pairs, while in the second one (university lecture) boring, long, stressful, notes, crowded, frontal teaching. Does this mean that university lectures might not be the students’ favourite way of learning, and they are not motivated enough anymore?
https://kmf.uz.ua/wp-content/uploads/2018/11/Multicult-Diversity_Book-of-Abstracts_23-10-2018.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006453
Keywords: university lecture; interactive lecture; ELTE